Интегральная модель трехмерного распределения вихревых токов в жидкой фазе непрерывнолитой заготовки при элетромагнитном перемешивании - Евдокимов, В.Ф.; Кучаев, А.А.; Петрушенко, Е.И.; Кучаев, В.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2011)
3D integral model of eddy currents and electromagnetic forces in the liquid phase of continuously cast billets with electromagnetic stirring is offered. Take into account the characteristics of the magnetic field of electromagnetic stirrer (EMS): currents low frequency 3...6 Hz in the EMS windings and electromagnetic forces field many times more magnetic fields of eddy currents. As a result we can neglect the magnetic field of eddy currents and assume that at each point of a massive conductor the magnetic field is equal to the magnetic field of EMS. In this case the initial system of integral equations is substantially simplified and its solution reduces to the solution of two subsystems: a vector integral equation for the density of the magnetization current on the surface of the EMS magnetic core and system of integral equations for the density of electric charges on the surfaces of massive conductors; in the resulting distribution of the density of electric charges is determined the electric scalar potential in the molten steel; from distribution of vector magnetic potential, the vector magnetic induction and the electric scalar potential in the liquid phase of billet is calculated the distribution of vectors of eddy currents density and electromagnetic forces.